Let's solve your equation step-by-step.<span><span><span>
2/3</span><span>(<span><span>3x</span>+1</span>)</span></span>=5</span>
Step 1: Simplify both sides of the equation.<span><span><span>
2/3</span><span>(<span><span>3x</span>+1</span>)</span></span>=5</span><span>
Simplify: (Show steps)</span><span><span><span>
2x</span>+<span>2/3</span></span>=5</span>
Step 2: Subtract 2/3 from both sides.<span><span><span><span>
2x</span>+<span>2/3</span></span>−<span>2/3</span></span>=<span>5−<span>2/3</span></span></span><span><span>
2x</span>=<span>13/3</span></span>
Step 3: Divide both sides by 2.<span><span><span>
2x/</span>2</span>=<span><span>13/3/</span>2</span></span><span>
x=<span>13/6</span></span>
Answer:<span>
x=<span>13/<span>6</span></span></span>
Answer:
36/52 or 9/13
Step-by-step explanation:
Ace-9 for all suits; Diamond, Hearts, Spades and Clubs
Answer:
a1= 1 q= −sinx , dla |q| <1 , ta suma jest zbieżna
a1 1
S=
=
1 −q 1+sinx
w mianowniku podobnie: a1=1 , q= sinx , dla | sinx| <1
1
S=
1 −sinx
i mamy równanie:
1
1+sinx
= tg2x
1
1− sinx
Step-by-step explanation:
Forty three million, eighty thousand, seven hundred
C. 10/x+8
The easy way to do it would be to take it one step at a time.